ASPERGILLOMA IN A PATIENT WITH NO PREVIOUS HISTORY OF CHRONIC LUNG DISEASE - Sheikh, Sadaf; Fatimi, Saulat Hasnain (Journal of Ayub Medical College Abbottabad, 2006)
Patients with aspergilloma should undergo surgical treatment, because there is a risk of sudden life threatening hemoptysis and because there is no effective alternate medical therapy. We report a case of aspergilloma in a 47 year old man with no past history of tuberculosis presented with the complaint of hemoptysis for two weeks. It was diagnosed radiologically and treated with left upper lobectomy. Post operative course was complicated by cardiorhythmic disorder. Keywords: Aspergilloma, Surgical resection, Cystic lesion